Public Opinion and Terrorist Acts - Jitka Malečková; Dragana Stanišić (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
The paper explores the dimensions of public opinion relevant for supporting terrorism and their relationship with terrorist attacks. We link the 2007 PEW survey data on justification of suicide terrorism and opinions in 16 countries of the Middle East, Africa and Asia on nine regional powers to the NCTC data on international terrorist incidents between 2004 and 2008. We find that justification of suicide terrorism and unfavorable opinion on regional powers are correlated with the occurrence of terrorism and the effect of each of these dimensions of public opinion varies with the level of the other. In addition, we find a robust positive relationship between the share of people in a country who at the same time justify suicide bombings and have an unfavorable opinion of a regional power and the occurrence of terrorism originating from that country.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: 330; support for terrorism; public opinion; international terrorism